Political calculations in subsidizing food - Hopkins, Raymond F. (International Food Policy Research Institute, 1988)
The role of the state in providing food subsidies to consumers has a long though sometimes ignoble history. In ancient Egypt, wheat prices were maintained by government storage schemes (chapter 13), and the value of cheap, ample food supplies for political stability was evidenced in the "bread and circus" era of the Roman Empire. However, detailed policy calculations connecting subsidies to production and nutritional status confront contemporary government leaders with ever more complex and confusing policy considerations (chapter 2).